The role of top-level sport in Finland : a governmental perspective of the present status and future trends - Westerlund, Juha (2011)
Top-level sports has been through its existance a part of Finnish society which creates social content. It has its own place in a nation’s history and culture. It has promoted national identity among Finnish people. This study examines the role and different faces of Finnish top-level sports during of its exisctance from early 1900s until today. In Today’s top-level sports there are many interesting aspects from which professionalism rises the topmost. From a governmental perspective the concept of top-level sport refers to sporting events and athletes who already represent their countries or aim at international success and recognition. Moreover such sports and athletes are also publicly subsidised. Today’s professionalised sport is viewed as generating both economic and social value for society, and it also has clear political value for the Finnish government. However, professionalised sport has also raised new ethical and moral questions which have directed government’s participation in top-level sport.